Indoor localization using narrow band ultrasonic sensors and frequency division multiple access - Chua, Bryan Jun Ping (2018)
The GPS (Global Positioning System), the most commonly used localization system, cannot be used for indoor localization due to its limitations. This project explores indoor 3D localization using narrowband ultrasonic chirp signals for its high accuracy in distance ranging and ability to implement FDMA (Frequency Division Multiple Access). The paper explores the 3 key concepts needed for the localization system. Literature review was done on each concepts before selecting the ideal implementation for the particular process of the localization system. A modified linear least squared algorithm was proposed as compensation due to limitations of the linear least square. The paper covered the tests conducted for comparison between the modified and original algorithms, and also accuracy test on the proposed ultrasonic localization system. Analysis of the test results were discussed to why they were observed and how future localization projects can use the results for future works in indoor localization projects.